Dekalog dalam Praktik Katekisasi sebagai pedoman bagi Generasi Z di era Digital - Virdo Manurung (Collecta: Jurnal Teologi dan Tradisi Kristen, 2024)
This study aims to affirm Decalogue teachings as guidelines for generation Z or digital natives. This is considered necessary to be reviewed specifically as the church’s efforts in guiding, educating, and teaching every member of the congregation, especially the congregation which can be called the future that will take over the entire instrument of church service. The decalogue in question refers to the ten commandments found in Exodus 20 and Deuteronomy 5. In Israelite culture, the Decalogue was God’s law to His people. The decalogue includes commandments categorized into two broad aspects: relationships to God and others. Decalogues are usually taught by the church in the discipleship process with the aim of maturing the faith which is often referred to as catechization. Since the beginning of Christianity, the teaching of the Decalogue has never been left to be taught to the disciples and that is what has always been maintained until the era of the arrival of missionaries to the archipelago, even today. Unfortunately, at present, the embodiment of Decalogue in the catechization process is only like a formality material, even though generation Z is considered very vulnerable to being hit by the bad influence of rapid digital progress, of course, this is a challenge that must be answered through the contribution of the role of the church. For this reason, this research is considered important, especially in the process of facing the digital era.